1997
DOI: 10.1046/j.1365-3083.1997.d01-141.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ‐Induced MHC Class I Expression and Defects in Jak/Stat Signalling in Methylcholanthrene‐Induced Sarcomas

Abstract: There was a tendency towards a higher MHC expression after IFN-g stimulation in tumour lines from immunocompetent mice compared to immunodeficient mice, but no common maximum MHC class I expression level was found for the 78 tumour cell lines. Three of the tumour lines, all from immunodeficient mice, completely failed to respond to IFN-g by up-regulating MHC class I expression. The same three also displayed absence of IFN-g-induced Stat1b tyrosine phosphorylation and low Stat1a tyrosine phosphorylation, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition to its role as a proinflammatory cytokine, IFN-␥ is capable of inducing MHC class I expression on a variety of cell types, including most tumor cells (28). The result of MHC upregulation on the surface of the tumor cells is recognition by CTL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role as a proinflammatory cytokine, IFN-␥ is capable of inducing MHC class I expression on a variety of cell types, including most tumor cells (28). The result of MHC upregulation on the surface of the tumor cells is recognition by CTL.…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 is a key transcription factor in IFN-␥ signaling processes and is known to regulate expression of class I and caspases in responsive cells (27,28). Because STAT1 controls the processes within cells that render them susceptible to CTL recognition and lysis, we asked whether differences in active STAT1 could account for the variation in class I expression and lytic susceptibility in the tumor cells following localized radiation.…”
Section: Deficient Ifn-␥ Signaling Limits Stat1 Phosphorylation Withimentioning
confidence: 99%
“…It was also reported that the sensitivity to IFN-␥ of tumor cells affects tumorigenicity, response to IL-12 therapy and anti-angiogenesis in mice (11). STAT1 is a regulator of gene transcription in the IFNs signaling pathway (12)(13)(14), and mutation of STAT1 can induce IFN-␥ insensitivity in tumor cells (15). The STAT1-dependent signaling is also important for expression of MHC class I in some cell types (16,17).…”
mentioning
confidence: 99%
“…2 Cytogenetic analysis of bone marrow aspirate at relapse 7 months after initial diagnosis showed translocation between short arm of chromosome 8 and 9 t(8;9)(p22; p24), as indicated by white arrowhead leukemogenesis. Data from in vitro studies showed a link between JAK2/Stat1 signaling pathway activation and MHC expression [22][23][24]. IFN-c induces tyrosine phosphorylation of the tyrosine kinases Jak1, Jak2 and of Stat1 alpha.…”
Section: Discussionmentioning
confidence: 99%